(untitled) - White, E. B. (New York, 1999)
The New York Times has named Here is New York one of the ten best books ever written about the metropolis, and The New Yorker calls it "the wittiest essay, and one of the most perceptive, ever done on the city.
Keywords: New York (N.Y.),New York (N.Y.); Description and travel.,Mô tả và du lịch